Determination of fluoride, zinc and lead ions concentrations in primary teeth and drinking water and dental caries experience - Zainab A. Al-Dahan; Baydaa A. Al-Rawi (University of Mosul, College of Dentistry, 2006)
Aims: To detect the levels of fluoride (F), zinc (Zn) and lead (Pb) in primary teeth and drinking water and their relation to dental caries experience in school children aged 6-12 years living in two distinct areas in Ninevah Governorate using two different sources of drinking water supply. Materials and Methods: The samples consisted of 120 freshly extracted highly mobile free of dental caries human primary mandibular teeth and ten wells water samples with ten tap water samples which had been chosen randomly. The samples were analyzed for F by fluoride sensitive electrode and for Zn and Pb by computerized atomic absorption spectrophotometer. Assessments and recording of caries experience were done by application of decayed, missing and filled surfaces (dmfs) index for primary dentition. Results: Statistical analysis of the results indicated that the mean F and Zn concentrations in the teeth were 244.35 + 167.49 ppm; 87.41+ 36.64 ppm respectively of the rural children were significantly higher than in the teeth of urban children (104.53 + 52.75 ppm; 65.19+ 28.79 ppm respectively). Meanwhile the concentration of Pb in the teeth of the urban children (1.62+0.41 ppm) was significantly higher than in the teeth of rural children (0.94+ 0.80 ppm)(p<0.001). Statistically significant higher F concentration in the wells water (3.39+ 0.25 ppm) than urban water supply (0.19+ 0.07 ppm) (p<0.001). Statistically significant higher Zn concentration in the urban water supply (0.1.34+ 0.31 ppm) than wells water (0.07+ 0.03 ppm) (p<0.001), but Pb concentration in wells water was not detected. Statistically significant higher caries experience was found in urban children than in rural (p<0.001). In the rural and urban areas, a negative correlation in the dmfs with F and Zn concentrations in teeth while a positive correlation with Pb was observed. Conclusions: A highly significant F and Zn concentrations in primary teeth were found in rural area than the urban and the opposite was true for Pb concentration. High significant F concentration was found in the wells water than urban water supply, and the opposite was true for Zn, but Pb concentration in wells water was not detected. High significant differences in dental caries indices were found in urban children than in rural children.